Locomotor Skills Development in Kindergarten: A Comparison Between Pencak Silat and Swimming (PIAUD IAIN Kudus, 2025)
Locomotor skills are the abilities that enable individuals to move efficiently and effectively from one location to another, encompassing both simple and complex movements. This study aims to explore the differences in locomotor skills among children participating in extracurricular programs, specifically pencak silat and swimming. A quantitative approach with an ex post facto design was employed, wherein data were collected through observation and analyzed using descriptive statistics, including mean observation scores and independent sample t-tests. The findings revealed a significant difference in locomotor skills between students engaged in pencak silat and those involved in swimming extracurricular activities. The swimming group achieved an average performance score of 2.3, categorized as adequate, while the pencak silat group attained an average score of 2.6, classified as good. These results indicate a disparity in locomotor skills between children participating in pencak silat and those in swimming extracurricular activities.